A crystal plasticity-based study of the relationship between microstructure and ultra-high-cycle fatigue life in nickel titanium alloys. (October 2016) - Moore, John A.; Frankel, Dana; Prasannavenkatesan, Rajesh; Domel, August G.; Olson, Gregory B.; Liu, Wing Kam
Highlights: A reconstructed inclusion image from serial sectioning was studied computationally. Fatigue crack nucleation potency near surfaces was amplified at low loads. Fatigue life was controlled by matrix yield strength over inclusion configurations. Abstract: Nickel Titanium (NiTi) alloys are often used in biomedical devices where failure due to mechanical fatigue is common. For other alloy systems, computational models have proven an effective means of determining the relationship between microstructural features and fatigue life. This work will extend the subset of those models which were based on crystal plasticity to examine the relationship between microstructure and fatigue life in NiTi alloys. It will explore the interaction between a spherical inclusion and the material's free surface along with several NiTi microstructures reconstructed from 3D imaging. This work will determine the distance at which the free surface interacts with an inclusion and the effect of applied strain of surface-inclusion interaction. The effects of inclusion–inclusion interaction, matrix voiding, and matrix strengthening are explored and ranked with regards to their influence on fatigue life.